Preliminary study of some development stages of the reproductive organs of Aegiceras corniculatum (L.) Blanco naturally growing in the coastal areas of north Vietnam - Hong Lien, Nguyen Thi; Hong, Phan Nguyen (Academia Journal of Biology, 2014)
Aegiceras corniculatum (L.) Blanco (Myrsinaceae) is a mangrove species living in tropical and sub-tropical estuarine coastal areas, bearing many features of adaption to the environmental conditions, especially the reproductive organs. This paper presents the time of formation and development of buds, seeds and propagules. It takes about 10 months in total for seeds to form the propagules, to develop and to fall from their parent trees. The seeds do not undergo the hypnosis period; they germinate into propagules right on their parent trees (semi-viviparous). The propagules possess roots and stems and receive nutrients from their parent trees through a haustorial system and the elongated placental stalk.